Unlocking Uncultivated Food for Mountain Livelihood: Case from Hindu Kush Himalayas - Aryal, Kamal; Kotru, Rajan; Phuntsho, Karma (Journal of Agriculture and Environment, 2013)
Throughout the Hindu Kush Himalayas, uncultivated plants provide a green social and cultural security to millions of people supporting their livelihood. Review on evaluating the multifunctional role of uncultivated plants in perspective of livelihood support finds that plants add diversity to local food systems, reinforce local culture and contribute diversity to farming systems, and finally are important for household food and nutrition security, social security, income generation and health care. Further, this paper clarifies that local people maintain and conserve diversity for the sake of use. The wise conservation and use of uncultivated plants are essential elements for increasing food security, eliminating poverty, and maintaining the environment. However, the value and potential of uncultivated plants for food and nutrition security, household level health care, income generation opportunity are not yet realized. Fast changing climate and early projections on its impacts suggest that such programmes must increasingly consider the sustenance of ecosystem that promotes uncultivated plants as basis for the welfare of millions.